Act together—implications of symbioses in aquatic ciliates - Dziallas, Claudia; Allgaier, Martin; Monaghan, Michael T.; Grossart, Hans-Peter (Frontiers in Microbiology, 2012)
Mutual interactions in form of symbioses can increase the fitness of organisms and provide them with the capacity to occupy new ecological niches. The formation of obligate symbioses allows for rapid evolution of new life forms including multitrophic consortia. Microbes are important components of many known endosymbioses and their short generation times and strong potential for genetic exchange may be important drivers of speciation. Hosts provide endo- and ectosymbionts with stable, nutrient-rich environments and protection from environmental stresses. This is of particular importance in aquatic ecosystems, which are often highly variable, harsh and nutrient-deficient habitats. Thus it is not surprising that symbioses are widespread in both marine and freshwater environments. Symbioses in aquatic ciliates are good model systems for exploring symbiont-host interactions. Many ciliate species are globally distributed and have been intensively studied in the context of plastid evolution. Their relatively large cell size offers an ideal habitat for numerous microorganisms with different functional traits including commensalism and parasitism. Phagocytosis facilitates the formation of symbiotic relationships, particularly since some ingested microorganisms can escape the digestion. For example, photoautotrophic algae and methanogens represent endosymbionts that greatly extend the biogeochemical functions of their hosts. Consequently, symbiotic relationships between protists and prokaryotes are widespread and often result in new ecological functions of symbiotic communities. This enables ciliates to thrive under a wide range of environmental conditions including ultraoligotrophic or anoxic habitats. We summarize the current understanding of this exciting research topic to identify the many areas in which knowledge is lacking and to stimulate future research by providing an overview on new methodologies and by formulating a number of emerging questions in this field.